The value of words. Restorative meetings between victims and convicted persons of terrorism crimes - Ríos Martín, Julián Carlos; Etxebarría Zarrabeitia, Xabier (Razón y fe, 2018)
The end of ETA, in addition to forever demolising a wall that has hidden death, destruction and moral ruin, also demands, from a situational ethics stance, the establishment of something natural by the so-called restorative justice. A justice that includes the satisfaction of the victims and the recovery of the offender and that, luckily, is being rehearsed, logically in small meetings between victims and perpetrators, in the Nanclares prison. Words, listening and dialogue constitute its bases.